FORMATION OF HYDROGEOLOGICAL-RECLAMATION SITUATION ON THE RICE IRRIGATION SYSTEMS OF THE DANUBE RIVER AND WAYS OF INCREASING THEIR ECONOMIC EFFICIENCY TAKING INTO ACCOUNT WEATHER AND CLIMATE RISKS - Rokochinskiy, A.; Turchenyuk, V.; Volk, P.; Prikhodko, N.; Frolenkova, N.; Shevchenko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The analysis of the main reasons for the unsatisfactory hydrogeological-reclamation state of the Danubian rice irrigation systems was carried out and the ways of its improvement due to the increase of drainage ability of irrigated lands of rice systems were considered. On the saline lands of the rice systems of the Danube delta drainage network is the main means of active and directed influence on the water-salt regime of the reclaimed area, formation of the regime of groundwater level, both in the growing season and in the not irrigated period for rice and attendant crops. Drainage network is essentially a determining factor in the formation of productivity of agricultural lands. An analysis of the efficiency of the drainage operation on the rice systems of the Danube Delta has shown that drainage built in accordance with the design standards that were in force at the time of construction does not provide uniform drainage ability in the area and the soil profile of rice fields. This is one of the main reasons for their unsatisfactory hydrogeological-reclamation state and reducing the yield of rice and attendant crops. By conducting optimization calculations according to the expense indicator, taking into account that optimal vertical filtration rate for the Danubian rice irrigation systems is at the level of 6...8 mm/day the optimal distance between the drains – 100 m was determined. Constructive improvement of existing rice systems with the drainage network in the form of open drains and distances between them – 250...500 m can be accomplished through the installation of additional separate closed drain-collectors. These drain-collectors are appropriate to arrange along the checks, with the set distance. For reducing the value of the vertical filtration rate in the drainage zone where it reaches 25 mm/day it is advisable to practice maintaining of water levels in the drainage network. Consequently, it is possible to achieve a reduction of the filtration rate to 4…5 mm/day. Developed measures and corresponding reconstruction of rice systems will enable to maintenance of satisfactory hydrological and hydrogeological regimes,ensure uniform salinity of soils during the cultivation of flooded rice, create favorable conditions for oxidation-reducing processes and maintenance of favorable ecological-reclamation state on the system.
Keywords: hydrogeological-reclamation state; rice irrigation system; filtration rate; drainage network; optimization